Dimensione dello spazio interno: l'opera 'luogo' in Arnaldo Pomodoro - Martina Soricaro (Annali Online dell'Università di Ferrara. Sezione Lettere, 2017)
This paper intends to analyze Arnaldo Pomodoro’s art work, particularly operations in which he has worked on a closed environment, an inner space, therefore far away from the monumental sphere that characterizes the artist's most famous operative codification. The works are not just placed in a place, but they are themselves "places", realized considering the historical-social context to which they are dedicated. In order to provide as wide a spectrum of Pomodoro's ability to read space as intended, were selected works in which the interplay between the site and the artist’s leap of imagination was translated into his personal expressive and symbolic language. Starting from sacred works (Corona radiante a Milwaukee, Altare per Pietrarubbia, Croce per San Giovanni Rotondo), in which Pomodoro has put himself through the wringer, defining an 'imaginary relationship' with the divine; followed by Cercatore Oscillante (Texas) and Rive dei Mari (Anacapri), where the artist interpreted the deepest sense of the place. Furthermore he represents the theme of the battle of human history, developed in the Sala d’Armi of Poldi Pezzoli Museum in Milan and in the great wallet Le Battaglie; in the end Ingresso nel labirinto, where the identification between work and 'place' is complete. It is a path, the one outlined by these works, which documents the tireless pursuit of one of the great interpreters of the sculpture of the second-twentieth century.